METALLURGICAL EDUCATION IN CDIO IDEOLOGY - Natalya V. Gafurova; Svetlana I. Osipova (Высшее образование в России)
The article discusses modernization of vocational education course “Metallurgy”, which aims at improving the competitiveness of a graduate in case of innovative variants of the Russian economy development. The authors define the factors that determine modernization of vocational education on a basis of the normative documents, national experience and international initiatives in the CDIO (Conceive – Design – Implement – Operate). The authors substantiate the system changes of vocational education that allow to implement competence-based approach and to create an innovative program, which deals with the crucial human and scientific problems through the integration of education, research and production activities in a public and private partnership.